Molecular dynamics simulation studies of mechanical properties of different carbon nanotube systems - Kok, Z. K. J. (2018)
Various mechanical properties of single-walled carbon nanotubes (SWCNT) and double-walled carbon nanotubes (DWCNT) are evaluated using molecular dynamics (MD) simulations. A tensioning process was first performed on a SWCNT whose interaction is based on the Brenner’s ‘second generation’ potential under varying length–diameter ratios and strain rates, in order to understand the SWCNT’s behaviour under axial tension. The results showed an increase in the SWCNT’s ultimate tensile strength and a decrease in critical strain given the conditions of increasing strain rate and a decreasing length–diameter ratio. Comparison was done with previous studies on axial tensioning of SWCNT to validate the results obtained from the set-up, based on the general stress–strain relationship and key mechanical properties such as the strain at failure and the Young’s modulus. A DWCNT was then constructed, and Lennard-Jones ‘12-6’ potential was used to describe the energy present between the nanotube layers. Extraction of the inner tube in a DWCNT was performed using two inner wall tubings of different diameters to draw comparison to the energies needed to separate fully the outer and inner tubing. Finally, a bending test was performed on two DWCNTs with different intertube separations. Insights into the entire bending process were obtained through analyses of the variations in the strain energy characteristic of the surface atoms near the bending site, as the DWCNT is gradually bent until failure.